ANALISA HASIL KINERJA PEGAWAI UNIVERSITAS STEKOM SEMARANG DARI PENGARUH KOMUNIKASI, MOTIVASI, DAN KEMAMPUAN KERJA - Ningsih, Pemilia Sulistyowati; Heni Susilowati (LPPM Universitas Sains dan Teknologi Komputer, 2020)
This research is to know the Influence of Communication, Motivation, And Work Ability To Performance Of Subdistrict Officer Of Universitas STEKOM Semarang. Research data was obtained through questionnaire. The sample used in this research is 82 respondents. The data obtained were processed by using descriptive analysis and quantitative statistical analysis. Quantitative analysis using multiple regression analysis to determine the effect of independent variables to dependent variables, but before the test is done first test the validity and reliability test.The result of regression analysis shows that Communication, Motivation, and Work Ability to Performance.